Implementation Digital Financial Technology in Supporting Financial Inclusion in CSR Fund Management in Pulau Ketam Conservation Area, Kuala Perlis Malaysia - Macia Sari, Maya; Ilmi Faried, Annisa; Fadhilah Sianipar, Hikmatul; Aini Binti Ibrahim, Ros; Nuraisyah, Julia (Action Research Literate, 2025)
This community service program aims to implement digital finance technology as an effort to strengthen financial inclusion in the management of Corporate Social Responsibility (CSR) funds within the Pulau Ketam Conservation Area, Kuala Perlis, Malaysia. The collaboration between Panca Budi Development University (UNPAB) and Tuanku Syed Sirajuddin Polytechnic (PTSS) is designed to empower local communities through the integration of financial technology (FinTech) solutions. The program focuses on enhancing community capacity in financial literacy, increasing transparency in CSR fund management, and supporting sustainable conservation activities. By applying participatory methods, training, and mentoring, this program provides a platform for local stakeholders to adopt digital financial applications effectively. The outcomes of this initiative include the improvement of financial management skills, strengthened accountability in CSR fund utilization, and the promotion of financial inclusion among marginalized groups. This program demonstrates that FinTech can serve as a strategic tool for community empowerment, sustainable development, and cross-border academic collaboration.